2014
DOI: 10.14503/thij-13-3350
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector Computed Tomographic Imaging of Erdheim-Chester Disease

Abstract: E rdheim-Chester disease (ECD) is a rarely reported form of multisystemic, non-Langerhans-cell histiocytosis. The clinical manifestations range from no symptoms to life-threatening conditions. Involvement of the bones, lungs, retro-orbital space, perirenal space, nervous system, cardiovascular system, and skin has particularly been observed. The cardiovascular involvement of ECD is probably more frequent than was originally thought; technological advances in multidetector computed tomography (MDCT) have enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“… 12 , 13 Second, myocardial localized or diffuse infiltration is often observed with frequent pseudotumoral infiltration of right atrium and involvement of the auricoloventricular sulcus. 14 , 15 Myocardial infiltration, in association with pericardial one, were both present in our patient. Moreover, coronary disease with myocardial infarction, valvular dysfunction, and heart failure have been described in the literature.…”
Section: Discussionsupporting
confidence: 56%
“… 12 , 13 Second, myocardial localized or diffuse infiltration is often observed with frequent pseudotumoral infiltration of right atrium and involvement of the auricoloventricular sulcus. 14 , 15 Myocardial infiltration, in association with pericardial one, were both present in our patient. Moreover, coronary disease with myocardial infarction, valvular dysfunction, and heart failure have been described in the literature.…”
Section: Discussionsupporting
confidence: 56%
“…Cardiovascular manifestations of ECD include pericardial effusion, tamponade, congestive heart failure, valvular disorders, renovascular hypertension, periaortic fibrosis, and myocardial infarction, as was the case in our patient’s history [ 5 ]. In a review of 72 cases of ECD, Haroche, et al demonstrated that 56% of patients had circumferential aortic encasement, the so-called “coated aorta” [ 6 ].…”
Section: Discussionmentioning
confidence: 87%
“…Due to its invasion of bilateral pararenal and perirenal space, “hairy kidney” is manifested. The typical CT of cardiovascular ECD shows soft tissue infiltration around the aorta, forming the “coated aorta” sign [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%